Enhancing the thermal conductivity and viscosity of ethylene glycol-based single-walled carbon nanotube (SWCNT) nanofluid: An investigation utilizing equilibrium molecular dynamics simulation - Shubhankar Sarkar; Papiya Pal; Nanda Kumar Ghosh (Chemical Thermodynamics and Thermal Analysis)
In this work, thermal conductivity (TC), viscosity, and rheological properties of an ethylene glycol (EG) based single-walled carbon nanotube (SWCNT) nanofluid (NF) have been computed using equilibrium molecular dynamics (EMD) simulation. In SWCNT, for the interaction between carbon atoms, Tersoff potential is used. Results indicate that TC and viscosity increase in nonlinear fashion with volume fraction. However, with temperature, TC increases but viscosity decreases. Increased interaction between CNT and liquid atoms of EG, and the high heat conductance ability of SWCNT nanoparticles enhance the effective conductivity and viscosity of NFs. Longer CNTs provide more efficient heat transfer pathways and more interactions between CNT & base fluid molecules, which contribute to enhanced TC and viscosity of NFs. Weakening of intermolecular forces within the NF with increasing temperature decreases viscosity. To validate the results, radial distribution function (RDF) and stress autocorrelation function (SACF) have been estimated. Mean square displacement (MSD) investigation demonstrates that the diffusion of liquid atoms (or molecules) serves as the fundamental mechanism for heat conduction in nanofluid. The results have been compared with experimental findings for analogous dispersive medium. Broadly, an attempt has been made to explore how interactions between the base fluid and nanoparticles (NPs) can enhance the thermal and rheological efficiencies of nanofluids.